ОБ ОБОБЩЕНИЯХ ВЕРХНЕЙ ПОЛУПЛОСКОСТИ В МНОГОМЕРНОМ КОМПЛЕКСНОМ ПРОСТРАНСТВЕ - Курбанов, Б.Т.; Каримбоев, Ж.Б. (SCIENCE and SOCIETY, 2024)
The work is devoted to the study of some problems of analysis on one multidimensional generalization of the upper half-plane, the boundary of which is the Poincaré sphere.
Keywords: generalization of the upper half-plane; multidimensional complex space; Poincaré sphere; multidimensional generalization